Case Report: Application of Percival’s Criterion in Correcting Insignificant Hyperopia in a Pre-Presbyope - Robertson, K M (Canadian Journal of Optometry, 1984)
This is a case report of simple hyperopia with adequate amplitude of accommodation to compensate for the increased accommodative stress. Success of the small prescription was attributed to the improved binocular function based upon Percival's criterion for vision comfort.